The forensic relevance of sexual fantasy: internal mental models, self-Representation and personality - Sowemimo, S. (2016)
Practitioners working within forensic environments will be acutely aware of the diverse risks, complex treatment needs and unique responsivity issues found within the multifaceted marginal group of sexual offenders. Deviant sexual fantasy (DSF) is considered to be important in the assessment and treatment of sexual offenders. Despite the recent growth in research, conclusions remain inconsistent on the significance of fantasy in offending behaviour. Furthermore, the underlying structural components of fantasy remain relatively unexplored. The aim of this thesis was to explore the forensic relevance of the fantasy phenomenon predominantly related to sexual offending populations. This was done by investigating the cognitive components of fantasy in regards to the intersection between fantasy, cognition, personality and self-representation (the latter constructs being considered as reflections of individual internal mental models).